The significance of refugees and asylum seekers to the European Pentecostal church. Issue 2 (3rd July 2019) - Hämäläinen, Arto
ABSTRACT: Recently the attitudes of Europeans have been tested about the many non-Europeans who have come into Europe. Thousands of people have flooded to the continent, challenging authorities and citizens in many countries. As part of society, churches have sometimes taken a strong, active role, whereas at other times, they have withdrawn, remaining as observers. What should be the healthy attitude of the church in this context, and especially that of the Pentecostals? Are there any statements given by Pentecostals in this matter? What have the Pentecostals done on the practical level? What is the theological basis for their actions? This paper paints a picture of the situation. The terms 'asylum seeker' or 'refugee', and sometimes the more general term of 'immigrant' are used to include all the various types of people coming from other countries.